2011
DOI: 10.1038/ncb2409
|View full text |Cite
|
Sign up to set email alerts
|

Bridging membrane and cytoskeleton dynamics in the secretory and endocytic pathways

Abstract: Transport carriers regulate membrane flow between compartments of the secretory and endocytic pathways in eukaryotic cells. Carrier biogenesis is assisted by microtubules, actin filaments and their associated motors that link to membrane-associated coats, adaptors and accessory proteins. We summarize here how the biochemical properties of membranes inform their interactions with cytoskeletal regulators. We also discuss how the forces generated by the cytoskeleton and motor proteins alter the biophysical proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
179
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(184 citation statements)
references
References 130 publications
1
179
0
4
Order By: Relevance
“…These vesicles followed a transport route from the apical membrane to the enterocytic lipid depots and hence seemed to be involved in endocytosis and intracellular transport of nutritional lipids. The GSL-dependent vesicle formation, essentially devoid of clathrin and Rab11, which are also involved in endocytosis and recycling processes (32)(33)(34)(35), might be unique for the intestine due to its high concentration of glycosphingolipids. The question whether GSL vesicles require proteins for their formation still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…These vesicles followed a transport route from the apical membrane to the enterocytic lipid depots and hence seemed to be involved in endocytosis and intracellular transport of nutritional lipids. The GSL-dependent vesicle formation, essentially devoid of clathrin and Rab11, which are also involved in endocytosis and recycling processes (32)(33)(34)(35), might be unique for the intestine due to its high concentration of glycosphingolipids. The question whether GSL vesicles require proteins for their formation still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that cytoskeletons have profound roles guiding and segregating membrane trafficking intermediates (5,(47)(48)(49). To further unravel the machinery underlying the dynamic hTAC tubules, we tested their dependence on the cytoskeleton.…”
Section: The Generation Of Htac-positive Tubules Requires Microtubulementioning
confidence: 99%
“…In addition, it has been demonstrated that clathrin and the adapter protein AP2 are involved in Ii down-regulation from the cell surface, and inhibition of clathrin-mediated down-regulation of Ii-MHC II complexes led to an increase in surface expression of Ii and a decrease of peptide-loaded MHC II complexes on the surface (McCormick et al, 2005). Hence, the accumulation of surface MHC II-Ii-p12in Cdc42 ko DCs could also represent a trafficking defect, especially because Cdc42 effector proteins were shown to be associated with clathrinmediated endocytosis (Anitei and Hoflack, 2011) and our own internalization assays revealed a decreased internalization rate of MHC. Although overall MHC II levels at the cell surface of immature Cdc42 ko BMDCs were not elevated, we found an increased proportion of Ii-MHC II complexes.…”
Section: Discussionmentioning
confidence: 99%